The Kidney Specific Protein myo-Inositol Oxygenase, a Potential Biomarker for Diabetic Nephropathy - Peng Gao; Bo Xu; Panai Song; Xuejing Zhu; Shuguang Yuan; Yashipal S. Kanwar; Lin Sun (Karger Publishers, 2018)
Background/Aims: Renal tubular injury plays an important role in the progression of diabetic nephropathy (DN). However, there is a lack of specific biomarkers for tubular damage in incipient DN. We have evaluated the role of myo-inositol oxygenase (MIOX) in the tubular injury of DN, but whether it could serve as a new biomarker for the early diagnosis of DN is unclear. Methods: Ninety patients with type 2 diabetes mellitus (T2DM) were divided into normoalbuminuria, microalbuminuria and macroalbuminuria groups. Fifteen patients from the last group were pathologically diagnosed as type 2 DN (T2DN), and fifteen patients with minimal change disease served as a control group. The expression of MIOX and silent information regulator 1 (Sirt1) in renal biopsies was determined by immunohistochemistry (IHC), and serum/urine MIOX, Sirt1, KIM-1 and NGAL were measured using enzyme-linked immunosorbent assays (ELISAs). Spearman's correlation and multiple regression analyses were carried out for statistical analyses. Results: Compared with the controls, MIOX expression was significantly increased in the renal tissues of T2DN patients, and was positively correlated with tubulointerstitial lesions and renal ROS production but inversely correlated with Sirt1 expression. In addition, the serum and urine MIOX were significantly increased and gradually elevated with the increasing of UACR. Interestingly, elevated MIOX levels in serum and urine were found in diabetic patients without early signs of glomerular damage (normoalbuminuric group). Further multivariate regression analysis showed that sMIOX and uMIOX correlated significantly with HbA1c, serum creatinine and logUACR, respectively. Conclusion: These data indicate that increased MIOX expression in the kidney contributes to tubular damage in DN. The concentration of MIOX in the serum and urine may serve as a new biomarker for the early diagnosis of DN.